Evaluation of open leadership and innovation orientation on employees and culture of the organization - Sönmez Çakır, Fatma; Adıgüzel, Zafer (Vilnius Gediminas Technical University, 2019)
In the production sector, where innovation and creativity activities are intensely realized, organizations need not only creativity activities but also process management in a successful organizational culture in order to be successful in the competitive environment in terms of both leadership and innovation activities. In terms of leadership, institutions need to be managed with a correct understanding. The aim of this study is to analyze the relationships between open leadership, innovation orientation, employee creativity, organizational culture and process management variables. In this study, the effects of open leadership role on innovation and employee creativity activities and process management were investigated. At the same time, innovation orientation mediated effect was demonstrated. In the scope of aim of the study, a survey was conducted with 418 engineers working in the production sector. IBM SPSS 25 program, LISREL program and SOBEL calculation tool were used in the analysis. The data obtained were evaluated. Confirmatory and explanatory factor analysis and reliability analysis were performed on questions used Likert scale. In this study, it is concluded that the mediation variable effect of innovation orientation variable is on both organizational culture and creativity and process management.
Keywords: Open Leadership; Innovation Orientation; Employee Creativity; Organizational Culture; Process Management; Production; Company